2009
DOI: 10.1159/000226283
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Evidence that Bedrest after Embryo Transfer Is Useless

Abstract: Background: To demonstrate the effect of immediate ambulation after embryo transfer on the intrauterine location of the transfer content. Methods: Prospective observational randomized controlled study. Results: Fifty-seven patients (47.5%) had one air bubble at transfer and after 15 min change in position: group A (bedrest) 2.69 mm, group B (immediate ambulation) 2.00 mm (p = 0.511). The distance from the fundus declined by 26% in group A and 15% in group B (p = 0.229). Twenty-eight patients (23.3%) had two ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
2
7
0
1
Order By: Relevance
“…Of all embryo(s) that implant successfully, 81% does so in the area where the air bubbles were initially seen on embryo transfer [28]. It is demonstrated that the air bubbles did not move after immediate ambulation after transfer in 94.1% of the cases [37] and this is confirmed by our study group [38]. We agree there is a lack of knowledge about positioning of the embryo(s) during and after embryo transfer in the uterine cavity, independently using a simple syringe or a new device.…”
Section: Discussionsupporting
confidence: 70%
“…Of all embryo(s) that implant successfully, 81% does so in the area where the air bubbles were initially seen on embryo transfer [28]. It is demonstrated that the air bubbles did not move after immediate ambulation after transfer in 94.1% of the cases [37] and this is confirmed by our study group [38]. We agree there is a lack of knowledge about positioning of the embryo(s) during and after embryo transfer in the uterine cavity, independently using a simple syringe or a new device.…”
Section: Discussionsupporting
confidence: 70%
“…This perspective was more common among less educated patients such that this finding may be explained by the association between less education and an increased likelihood of considering any lifestyle choice impactful. Notwithstanding, both findings demonstrate that despite insufficient evidence to support its use [6,7,12], bed rest remains a topic of concern for many IVF patients.…”
Section: Discussionmentioning
confidence: 93%
“…Studies suggest certain lifestyle behaviors and patient characteristics such as being underweight or obese adversely affect cycle success [2,3], while stress-reducing behaviors are generally thought to be beneficial [4,5]. Meanwhile, some popularly supported behaviors, such as complete bed rest after embryo transfer, have not been shown to improve outcomes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…After transfer of fertilized embryos into the uterus via a small catheter, patients are often told to remain in the supine position for 30 minutes and minimize activity for the remainder of the day. Two prospective RCTs have assessed the benefit of bed rest after embryo transfer; no difference in uterine contents directly after transfer42 or clinical and ongoing pregnancy rates43 were evident between the 2 study groups of bed rest and immediate ambulation. A Cochrane review in 2009 further reported insufficient evidence in the literature to support the recommendation of bed rest after embryo transfer for in vitro fertilization 44…”
Section: Clinical Conditions For Which Bed Rest Is Prescribedmentioning
confidence: 99%